Yijie Zhu: capstone - Zhu, Yijie, artist (Colorado State University. Libraries, 2018)
The artist's statement: As a graphic designer, I use a lot of different mediums to reach a perfect result. I take care of every step and keep myself creative when seeking more ideas. I use the Adobe Suites to complete some special but necessary edits to express the final work. To make my work creative and interesting, I hide some meaning behind the work. I would like my viewers can think about my work for a while and then find the "meaning" by themselves. I won't set a "right" answer for my work to encourage my viewers to have more unique experiences of my work. I believe that design can change the world by showing a different and more interesting world. I wish that my works can be their guide, giving them a new look at the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.